Cocreated internet‐based stepped care for individuals with cancer and concurrent symptoms of anxiety and depression: Results from the U‐CARE AdultCan randomized controlled trial. Issue 12 (22nd September 2020) - Hauffman, Anna; Alfonsson, Sven; Bill‐Axelson, Anna; Bergkvist, Leif; Forslund, Marina; Mattsson, Susanne; von Essen, Louise; Nygren, Peter; Igelström, Helena; Johansson, Birgitta
Abstract: Objective: The aim was to evaluate the effects of cocreated internet‐based stepped care (iCAN‐DO) on anxiety, depression, posttraumatic stress, and health‐related quality of life (HRQoL) in individuals with cancer and self‐reported anxiety and/or depression symptoms, compared with standard care. Methods: Clinically recruited individuals with breast, colorectal, or prostate cancer underwent online screening with the Hospital Anxiety and Depression Scale (HADS). Those with anxiety and/or depression symptoms (>7 on any of the HADS subscales) were randomized to iCAN‐DO or standard care. iCAN‐DO comprised psychoeducation and self‐care strategies (step 1) and internet‐based cognitive behavioral therapy (iCBT, step 2). Data were collected before randomization and at 1, 4, 7, and 10 months and analyzed with intention‐to‐treat regression analysis and randomization tests. Results: Online screening identified 245 (27%) of 909 individuals who reported anxiety and/or depression symptoms. They were randomized to iCAN‐DO (n = 124) or standard care (n = 121). Of them 49% completed the 10‐month assessment, and in the iCAN‐DO group 85% accessed step 1 and 13% underwent iCBT. iCAN‐DO decreased the levels of symptoms of depression (−0.54, 95% confidence interval: −1.08 to −0.01, P < .05) and the proportion of individuals with symptoms of depression ( P < .01) at 10 months, compared with standard care, according to HADS. There were no significant effects on anxiety, posttraumatic stress, or HRQoL. Conclusion: Internet‐based stepped care improves symptoms of depression in individuals with cancer. Further studies are needed to gain knowledge on how to optimize and implement internet‐based support in oncology care.